2008
DOI: 10.1007/s10832-008-9548-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-doped CaO/MnO on the piezoelectric/dielectric properties and phase transition of lead-Free (Bi0.5Na0.5)0.94Ba0.06TiO3 piezoelectric ceramics

Abstract: The piezoelectric properties of (1−x)(Bi 0.5 Na 0.5 ) TiO 3 -xBaTiO 3 ceramics were reported and their piezoelectric properties reach extreme values near the MPB (about x= 0.06). The X-ray analysis of (Bi 0.5 Na 0.5 ) 0.94 Ba 0.06 TiO 3 ceramics for all compositions exhibited a pure perovskite structure without any secondary phase. Within a certain ratio of contents, the co-doped ceramics enhanced piezoelectric coefficient (d 33 ), lowered the dielectric loss, and increased the sintered density. The temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…13 shows the temperature dependence of the dielectric properties with various amounts of excess Ba. The dielectric behavior is rather analogous to those previously observed in BNBT ceramics with MPB compositions [30]. The inflection point designated T d in Fig.…”
Section: Effects Of the Excess Barium On The Piezoelectric/ Dielectrisupporting
confidence: 81%
“…13 shows the temperature dependence of the dielectric properties with various amounts of excess Ba. The dielectric behavior is rather analogous to those previously observed in BNBT ceramics with MPB compositions [30]. The inflection point designated T d in Fig.…”
Section: Effects Of the Excess Barium On The Piezoelectric/ Dielectrisupporting
confidence: 81%
“…Also, when comparing real values of all elastic s E ij coefficients and the frequency numbers it is observed that BNBT4 ceramic is similar to BNBT6 from the mechanical point of view, but the losses are also lower. Table III Besides these interesting properties and just as an example among the many studies on doping BNBT ceramics to enhance electromechanical performance, CaO/MnO co-doping [24] has shown efficiency in increasing d 33 , k p and k t . At the same time the depolarization temperature is almost unchanged, the sinterability increases and the grain size of the ceramics is reduced.…”
Section: Electromechanical Properties At Room Temperaturementioning
confidence: 99%
“…[8,12,17,19,21,22,24,25,28,36,37,43,46,47,54,60,62,63,67,69,76] According to Liu and Ren [27], a large piezoelectricity of this system is due to the existence of cubic-rhombohedral-tetragonal (C-R-T) triple point, as depicted in Fig. 9.4.…”
Section: Barium Titanatementioning
confidence: 99%
“…The transitions from cubic to tetragonal, tetragonal to orthorhombic, and then orthorhombic to rhombohedral occur at 435, 225, and À10 C, respectively [35,61]. KNbO 3 (KN) and NaNbO 3 (NN) can form a solid solution over the whole composition range and undergo similar structural phase transitions to KN upon [8,12,21,24,25,36,54,60,62,63,67,76] cooling (see Fig. 9.8).…”
Section: Knn and Modified Knn Systemmentioning
confidence: 99%
See 1 more Smart Citation